Why Tongues? The Initial Evidence Doctrine in North American Pentecostal Churches - Walters, Kenneth Richard, (Journal of Pentecostal Theology Supplement Series ;, 2016)
The modern Pentecostal movement has been studied many times in relation to its theological and sociological background. Previous studies, however, have not focused on the disctinctive doctrine of that movement: the teaching that speaking in tongues is the initial physical evidence of the Baptism in the Holy Spirit. Given that Pentecostals believe that this is a work of grace, such a doctrine seems unlikely to arise, as physical evidence is seldom required or looked for in the life of a believer in relation to any other area of grace. This prompts the question of why such evidence was even being looked for. And yet, within a very short time of its proposal, acceptance of this doctrine was so widespread as to become the hallmark of the movement. Insistence on such a doctrine led to many being asked to leave their denominations, and thus to the founding of other denominations. This book attempts to answer the question: "Why?" And specifically: "Why Tongues?"